2011
DOI: 10.1103/physrevb.84.140102
|View full text |Cite
|
Sign up to set email alerts
|

Strain glassy behavior and premartensitic transition in Au7Cu5Al4alloy

Abstract: Strain glassy behavior (SGB) in correlation with premartensitic tweed (PMT) morphology was observed in an Au 7 Cu 5 Al 4 alloy, which is different from previously observed SGB that is incompatible with PMT in doped Ti-Ni alloys. Additionally, an "inverse freezing" transition from martensite to premartensitic strain glass upon heating was experimentally discovered, confirming a recent theoretical prediction. Investigations of rich phenomena in nonmagnetic Au-Cu-Al alloys are expected to shed light on the origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Ren and collaborators [12][13][14] suggested that the premartensitic tweed is a frozen 'strain glass' stems from point defects (such as the doping excess atoms), which is similar to the proposal of Kartha et al [2,10] and Loveras et al [1]. Our previous paper [15] and Zhang [14] have experimental proved that the premartensitic tweed indeed shows the 'strain glassy behavior' in Au-Cu-Al alloys and Ti-Ni-based alloys, respectively.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Ren and collaborators [12][13][14] suggested that the premartensitic tweed is a frozen 'strain glass' stems from point defects (such as the doping excess atoms), which is similar to the proposal of Kartha et al [2,10] and Loveras et al [1]. Our previous paper [15] and Zhang [14] have experimental proved that the premartensitic tweed indeed shows the 'strain glassy behavior' in Au-Cu-Al alloys and Ti-Ni-based alloys, respectively.…”
Section: Introductionsupporting
confidence: 69%
“…The premartensitic tweed in Au-Cu-Al alloys was reported in our previous paper [15]. In the present work aiming to a better understanding of the origin of premartensitic tweed, the BCC parent (L2 1 -type β phase) → BCC (Cu 9 Al 4 -type premartensitic phase) transition giving rise to the tweed morphology was investigated further detailedly.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Based on this concept, Kartha et al and Ren and collaborators developed the theory and proposed the “spin/strain glass nature” of premartensitic tweed due to frozen point defects or intrinsic compositional disorder. Also, our previous paper and Zhang et al have experimentally proved that the premartensitic tweed or mottled phase indeed shows the “strain glass behavior” in Au–Cu–Al and Ti–Ni‐based alloys respectively.…”
Section: Introductionmentioning
confidence: 66%